Structural performance of additive manufactured wood-sodium silicate composite beams for sustainable construction - Hematabadi, Hojat; A Alade, Adefemi; HR Carne, Robert; Robertson, Daniel; Yapa, Milinda; G. McDonald, Armando; A. Ibrahim, Ahmed (Sustainable structures, 2024)
The current research examines the structural bending performance of additive manufactured wood-sodium silicate composite beams of various span-to-height proportions. Beams consisting of both a single layer as well as two layers of extruded wood-sodium silicate composite were considered. Both groups of beams exhibited a rise in maximum shear force (Vmax), maximum bending moment (Mmax), apparent modulus of elasticity (MOEapp), and modulus of rupture (MOR) when the span-to-height proportions rose. However, the amount of shear stress (τmax) decreased as the span-to-height proportion increased. Furthermore, the flexural and shear stress patterns for span-to-height proportions of 6 and 30 were calculated analytically using the transformed section methodology across the thickness of the beams at different positions of L/6, L/3, 5L/12, and L/2 of the beam span. The results demonstrated that the bending stress increased as the distances from the supports increased toward the middle of the beam. Compared to single-layer beams, two-layer beams displayed lower stress values overall. In particular, the bending stress was 4.85% lower in the two-layer beam with a span-to-height proportion of 6 than that of the single-layer beams. Furthermore, the single-layer beam's maximum shear stress was slightly greater than the two-layer beams. The greatest shear stress of the single-layer beams were computed 4.27% and 0.46% higher than those of the two-layer beams at span-to-height proportions of 6 and 30, respectively.